Almost sure scattering for the energy-critical NLS with radial data below H1(R4). Issue 1 (2nd January 2019) - Killip, Rowan; Murphy, Jason; Visan, Monica
Abstract: We prove almost sure global existence and scattering for the energy-critical nonlinear Schrödinger equation with randomized spherically symmetric initial data inH s ( R 4 ) with5 6 < s < 1 . We were inspired to consider this problem by the recent work of Dodson–Lührmann–Mendelson, which treated the analogous problem for the energy-critical wave equation.